2015
DOI: 10.5194/gmdd-8-615-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A generic approach to explicit simulation of uncertainty in the NEMO ocean model

Abstract: Abstract. In this paper, a simple and generic implementation approach is presented, with the aim of transforming a deterministic ocean model (like NEMO) into a probabilistic model. With this approach, several kinds of stochastic parameterizations are implemented to simulate the non-deterministic effect of unresolved processes, unresolved scales, unresolved diversity. The method is illustrated with three applications, showing that uncertainties can produce a major effect in the circulation model, in the ecosyst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…Despite this, the impact of stochastic perturbations and their evolution depends strongly on the model horizontal resolution, the time‐scale considered, and the atmospheric forcing variability (for example, Williams, ; Brankart, ; Brankart et al. ; Andrejczuk et al. ; Williams et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, the impact of stochastic perturbations and their evolution depends strongly on the model horizontal resolution, the time‐scale considered, and the atmospheric forcing variability (for example, Williams, ; Brankart, ; Brankart et al. ; Andrejczuk et al. ; Williams et al.…”
Section: Discussionmentioning
confidence: 99%
“…), with a focus on the stochastic effect of unresolved scales in the computation of density (as in Brankart et al. ; see section 3.2 for results). The original purpose of these ensemble simulations was to investigate to what extent uncertain model operators can be made statistically consistent with observations (for example, satellite altimetry or Array for Real‐time Geostrophic Oceanography (ARGO) floats).…”
Section: Diversity Of Ocean Ensembles and Uncertaintymentioning
confidence: 99%
“…The study of Weisheimer et al [2011] compared the multi-model, perturbed parameter and atmospheric stochastic physics approach for monthly and seasonal forecasts showing the potential for stochastic parametrizations to outperform the multi-model ensemble.The motivation for stochastic parametrizations in the atmosphere originates to some degree from the existence of power law structures and the related rapid upscale error propagation [see Palmer , 2012, for a detailed discussion]. Since similar power law structures, associated with mesoscale eddies, can also be found in the ocean [LaCasce and Ohlmann, LaCasce, 2008] similar arguments for the potential role of stochastic parametrizations may therefore hold.Stochastic parametrizations have not only been introduced into the atmospheric component of NWP and seasonal forecast models [e.g.,Buizza et al, 1999; Palmer et al, 2009], but have more recently also been implemented into the sea ice[Juricke et al, 2013;Juricke and Jung, 2014], ocean [e.g.,Brankart, 2013;Brankart et al, 2015], land surface [MacLeod…”
mentioning
confidence: 99%
“…In order to avoid uncertainties from employing deterministic parameter estimations, Brankart () showed that the application of stochastic parameterization in the seawater equation of state can produce a notable effect on the average large‐scale circulation of the ocean, with a more prominent signal in regions of high mesoscale activity. Next, Brankart et al () investigated unsolved processes and scales of the ocean model through stochastic temperature (T) and salinity (S) fluctuations and noted that the small scales constantly modify the structure of the large‐scale density, and thus the pathway of the large‐scale circulation, as a result of the nonlinearity of the equation of state. Brankart et al () also mentioned but did not investigate the uncertainties derived from external forcing such as the atmospheric forcing, river runoff, or lateral boundary conditions.…”
Section: Introductionmentioning
confidence: 99%